Unveiling pterion variability: a meta-analytic approach to enhance neurosurgical precision. - Triantafyllou, George; Karangeli, Nektaria; Duparc, Fabrice; Piagkou, Maria; Galzio, Renato; Tsakotos, George; Botis, George; Kalamatianos, Theodosis; Luzzi, Sabino (Surgical & Radiologic Anatomy, 2025)
Purpose: This meta-analytical systematic review aims at investigating the variability of the pterion, focusing on its morphological types and precise distances from various bony landmarks. Additionally, the neurosurgical significance of this critical cranial landmark is examined in depth. Methods: The systematic review was conducted following PRISMA 2020 and Evidence-based Anatomy Workgroup guidelines for anatomical studies. The risk of bias was assessed using the Anatomical Quality Assurance Tool (AQUA). The meta-analysis was performed using R programming software and RStudio, employing the "meta" and "metafor" packages. Results: A total of 79 studies were included, encompassing 18,694 skull sides. The sphenoparietal type was identified as the most prevalent pterion variant, with a pooled prevalence of 78.54%. The epipteric type followed at 8.41%, while the frontotemporal (5.74%) and stellate (4.26%) types were the rarest. Significant differences in the prevalence of the epipteric, frontotemporal, and stellate types were observed across different nationalities. However, sex, side, and study type did not significantly influence pterion morphological variation. The study also extracted and calculated the distances between the pterion and key anatomical landmarks, including the midpoint of the zygomatic arch, the frontozygomatic suture, the mastoid process, and the external acoustic meatus. Conclusion: This study offers critical anatomical insights by accurately mapping the pterion's location relative to essential cranial landmarks. These findings are vital for neurosurgical planning, particularly for procedures involving the anterior and middle cranial fossae. The detailed anatomical data provided can enhance the precision and safety of neurosurgical interventions, ultimately improving patient outcomes.